Effect of ozone gas on cultures of Candida albicans and Aspergillus fumigatus: evaluation of two ozonation devices - Caetano, Maicon Henrique [UNESP]; Ferreira, Adriano Menis; de Andrade, Denise; Lopes de Sousa, Álvaro Francisco; Carneiro, Liliane Moretti; Barbosa, Alessandra Lyrio; Félix de Carvalho, Herica Emilia; Rigotti, Marcelo Alessandro; Gottardo de Almeida, Margarete Teresa (Journal of Infection in Developing Countries, 2024)
Introduction: Candida albicans and Aspergillus fumigatus are two important agents of Healthcare-associated infections. This study aimed to evaluate the antifungal activity of ozone (O3) gas produced by two commercial devices against cultures of these two species. Methodology: Sterile plastic plates were inoculated with C. albicans and A. fumigatus and placed on a countertop at three distances (30 cm, 1 m, and 2 m) and three positions in relation to the wall (near, middle, and away), considering the source of O3. Plates were exposed to O3 for one hour and incubated. After incubation, the counting of colony-forming units was performed. As a control, an inoculated plate was incubated, without being exposed to O3. Tests were carried out with two different devices (namely, Mod.I and Mod.II), with the air conditioner on and off, in triplicate. Results: Both devices showed antifungal activity. Mod. I presented better results, due to a higher flow rate. The best activity was on plates at 30 cm, middle position. Contrarily, on plates at 2m, near the wall, the inhibition activity was lower. The best results were obtained with the air conditioner off. Candida albicans was more sensitive to O3 than A. fumigatus. Conclusions: This method of decontamination by O3 gas shows potential due to its fast and easy execution. The establishment of new protocols for hygiene and hospital disinfection using this approach should be considered, which may reduce environmental contamination by fungi and, consequently, the burden of fungal infections.
Keywords: Aspergillus fumigatus; Candida albicans; disinfection; ozonation; Ozone